The Role of Saudi Universities in Facilitating the Understanding of National Dialects: A Critical Statistical Study - Al Asmari, Jawhara; Al-Basalah, Aida; Al-Shahrani, Shamsah; Al Mughaira, Haya Ali; Al-Fayez, Munira Abdullah (مجلة العلوم التربوية والدراسات الإنسانية سلسلة الآداب والعلوم التربوية والإنسانية والتطبيقية, 2025)
This study explores the role of Saudi universities in helping non-Arabic speakers understand national dialects. A descriptive analytical approach was used, focusing on a random sample of students learning Arabic as a second language. The key findings reveal that universities play a positive and statistically significant role in facilitating dialect comprehension in Saudi Arabia. There is a clear connection from educational goals to implementation mechanisms, and from these mechanisms to various difficulties and challenges encountered by learners. However, there is no statistically significant relationship between the difficulties and challenges and improvements in dialect understanding. The study also found a high level of agreement among respondents on the questionnaire statements. It concludes with a recommendation to link improvement plans and mechanisms to the identified difficulties and challenges. Additionally, it suggests creating programs that promote cross-cultural exchange and teach languages in their various dialects, utilizing computer programs and digital media. This approach aims to support and encourage innovation through smart applications, thereby facilitating the understanding of both classical Arabic and its dialects.